Estudo da diversidade química das folhas de Spondias tuberosa durante os estádios de evolução fenológicos: abordagens metabolômica e quimiométrica associadas as atividades antioxidante e antiglicante - Nascimento, Francisco Wendell Moreira do (2024)
Spondias tuberosa Arr. Cam. popularly known as umbuzeiro, is an endemic species of the Caatinga, belonging to the Anacardiaceae family. Umbuzeiro food species present studies that cover areas of science, such as Chemistry of Natural Products, Pharmacology, presenting relevant biological activities of interest to the industry. In this context, the search for antioxidant and anti-aging substances by the cosmetics industry is justified by the need for more effective skin protectors, capable of inhibiting the oxidative deterioration of labile ingredients, such as unsaturated fatty acids or other skin active ingredients, prone to oxidation. There is a major bottleneck in chemical studies for this genus, which is related to the metabolic variations of the same species during different stages of phenological evolution. The ultra-performance liquid chromatography technique coupled to high-resolution mass spectrometry UPLC-QToF-MSE in negative ionization mode was used to trace the chemical profile of S. tuberosa leaves at different phenological stages, and also with the aid of chemoinformatics tools a chemical study was designed in order to obtain maximum information regarding the phenological development in the three phases of the leaf, namely: the post-flowering phase (young leaf), full production and senescence. Of the classes of metabolites noted, phenolic compounds stand out, which were the majority, such as glycosylated flavonoids and aglycone, ellagitannins and anacardic acids. The antiglycant activity assay revealed a potential inhibition of the formation of AGEs in the leaves at different stages of phenological development, which, through an analysis of variance (ANOVA), made it possible to state that there was no significant difference between the means of AGE activity in each phase. The antioxidant activity was satisfactory and in agreement with previously reported results. The study was able to highlight the potential use of umbuzeiro leaves as an alternative source of natural antioxidants, applicable in anti-aging formulations, making it possible to use the leaves of this species, which are currently completely discarded, and can provide an increase in added value to umbuzeiro cultivation. , stimulating family farming and the recovery of tree density in degraded areas.